2016
DOI: 10.1016/j.jad.2015.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation and depressive symptoms at 1-, 3-, 6-, and 12-months follow-up

Abstract: Smoking cessation is associated with a decrease in depressive symptomatology, that is maintained over time. In contrast, relapse is associated with an increase of such symptoms. These findings signify the potential importance of addressing depressive symptomatology in smoking cessation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 42 publications
(50 reference statements)
2
24
0
3
Order By: Relevance
“…The findings on a reduction in depressive symptoms in those who abstain from smoking also support previous findings from a small clinical study [10] and are in line with 1 n = 346 with moderate depression (BDI-II score 20-28): 25.7% abstinence; n = 173 with severe depression (BDI-II score ≥29): 26.0% abstinence 2 n = 292 with primary school: 27.7% abstinence: n = 2136 with secondary school: 35.3% abstinence 3 n = 47 with bupropion only: 47% abstinence: n = 79 with NRT and bupropion: 44% abstinence 4 Includes n = 80 varenicline + bupropion (no e-cigarette): 45% abstinence; n = 21 varenicline + bupropion + NRT (no e-cigarette): 43% abstinence; n = 30 e-cigarettes in any combination (n = 25) or exclusively (n = 5): 50% abstinence n = 72 used 'paipo' in any combination (n = 60) or exclusively (n = 12): 49% abstinence. This was not treated as pharmacotherapy in analysis and not taken into account for categorisation findings of a meta-analysis [9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings on a reduction in depressive symptoms in those who abstain from smoking also support previous findings from a small clinical study [10] and are in line with 1 n = 346 with moderate depression (BDI-II score 20-28): 25.7% abstinence; n = 173 with severe depression (BDI-II score ≥29): 26.0% abstinence 2 n = 292 with primary school: 27.7% abstinence: n = 2136 with secondary school: 35.3% abstinence 3 n = 47 with bupropion only: 47% abstinence: n = 79 with NRT and bupropion: 44% abstinence 4 Includes n = 80 varenicline + bupropion (no e-cigarette): 45% abstinence; n = 21 varenicline + bupropion + NRT (no e-cigarette): 43% abstinence; n = 30 e-cigarettes in any combination (n = 25) or exclusively (n = 5): 50% abstinence n = 72 used 'paipo' in any combination (n = 60) or exclusively (n = 12): 49% abstinence. This was not treated as pharmacotherapy in analysis and not taken into account for categorisation findings of a meta-analysis [9].…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to these concerns, a recent systematic review and meta-analysis of longitudinal studies found that compared with continuing to smoke, quitting smoking was associated with a significant decrease in depression from baseline to follow-up [9]. This is corroborated by recent findings from smoking cessation practice indicating continuous improvements in depression symptoms over 1 year among those who quit smoking and no change in those who continued to smoke [10]. However, in a longitudinal study in older smokers, quitting smoking had no impact on depression [11].…”
Section: Introductionmentioning
confidence: 93%
“…A systematic review of 26 studies focused on smoking cessation and mental health revealed that quitting smoking led to decreased anxiety, stress, and depression, with an increased positive mood [63]. Smoking cessation is also associated with longitudinal improvement in physical quality of life [64,65] and a decrease in depressive symptomatology [66,67], and a decrease in other risky behaviors, such as alcohol consumption [68].…”
Section: Discussionmentioning
confidence: 99%
“…35,36 A study reported that smoking cessation led to depression, 37 suggesting that it might be better to let depressed patients smoke, thereby discouraging the smoking cessation recommendation to these patients. However, given mounting evidence on how to treat smoking patients with mental disorders, 38 and the latest empirical evidence suggesting that smoking cessation actually decreases depression, 39,40 it is worth focusing more on smoking cessation among patients with conditions such as depression.…”
Section: Discussionmentioning
confidence: 99%